2020
DOI: 10.1186/s12903-020-01068-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of sugar-sweetened drinks with caries in 10- and 15-year-olds

Abstract: Background: Sugar-sweetened drinks (SSDs) are known to be cariogenic, but this association has not been well investigated in population-based repeated cross-sectional studies in recent years. Therefore, this study examined whether SSD intake is associated with higher caries experience in 10-and 15-year-olds. Methods: The study sample included participants from the Munich study centre of two birth cohorts with data on non-cavitated caries lesions (NCCL/S), caries experience (DMF/S index), overall caries burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Thus, carbohydrates that are rapidly digested and give rise to high blood glucose concentrations are perceived as of lower quality compared with carbohydrates that are more slowly digested and result in lower blood glucose concentrations over time. Free sugars are to be avoided because they are associated with processed foods (such as sugar‐sweetened beverages) linked to overweight and obesity, and because they have a high cariogenic potential (Blostein et al., 2020; Pitchika et al., 2020). The glycemic index (GI) and glycemic load (GL) metrics have been widely applied as indicators of this aspect of dietary carbohydrate quality but are often criticized for not representing responses to complex food mixtures.…”
Section: Effects Of Whole Grains On Dietary Carbohydrate Qualitymentioning
confidence: 99%
“…Thus, carbohydrates that are rapidly digested and give rise to high blood glucose concentrations are perceived as of lower quality compared with carbohydrates that are more slowly digested and result in lower blood glucose concentrations over time. Free sugars are to be avoided because they are associated with processed foods (such as sugar‐sweetened beverages) linked to overweight and obesity, and because they have a high cariogenic potential (Blostein et al., 2020; Pitchika et al., 2020). The glycemic index (GI) and glycemic load (GL) metrics have been widely applied as indicators of this aspect of dietary carbohydrate quality but are often criticized for not representing responses to complex food mixtures.…”
Section: Effects Of Whole Grains On Dietary Carbohydrate Qualitymentioning
confidence: 99%
“…In other countries, adolescents have been found to consume sweets considerably less frequently [ 51 , 52 ]. A study carried out in Germany confirmed that the intake of beverages was significantly associated with DMF-S score among 15-year-olds [ 55 ]. With respect to oral health, these are noteworthy findings because high consumption of added sugar may lead to higher prevalence of periodontal diseases and increase the risk of dental caries [ 1 , 56 ].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, the effects of sucrose appear to be of great concern during childhood, given the fact that SSBs intake significantly increases the caries burden in 10-year-olds with attenuated effects in 15-year-olds-age groups that are known to be the highest consumers of free sugars. To prevent caries, SSBs consumption should therefore be reduced, especially in children and adolescents (95). Of great concern are a simultaneous combination of high sipping frequency and low PH beverage and sugar concentration, especially in young children, leading to early childhood caries.…”
Section: Sugars and Oral Healthmentioning
confidence: 99%